Pengabdian Kepada Masyarakat Melalui Penyuluhan Swamedikasi Diare Pada Anak Di Kampung Baru - Delladari Mayefis; Arie Vonikartika; Henny Rachdianti T S; Nurlia Oktaviyanti (Jurnal Pengabdian Ilmu Kesehatan, 2021)
Diarrhea, a global issue, particularly affects children under 5 and is a leading cause of death as per WHO. Self-medication for diarrhea is rising due to its impact on daily life. To address this, outreach efforts targeted parents with children under five, conducted by Mitra Bunda Health Institute. Involving lecturers, students, and 100 community members, the initiative ran from September 2020 to February 2021. It began with assessing participants' knowledge, followed by education on self-medication including ORS and probiotics. Health checks were also conducted on children. Post-counseling, a knowledge evaluation was done to enhance awareness and promote proper health practices.